2023
DOI: 10.3390/cells12060879
|View full text |Cite
|
Sign up to set email alerts
|

The Tobacco Smoke Component, Acrolein, as a Major Culprit in Lung Diseases and Respiratory Cancers: Molecular Mechanisms of Acrolein Cytotoxic Activity

Abstract: Acrolein, a highly reactive unsaturated aldehyde, is a ubiquitous environmental pollutant that seriously threatens human health and life. Due to its high reactivity, cytotoxicity and genotoxicity, acrolein is involved in the development of several diseases, including multiple sclerosis, neurodegenerative diseases such as Alzheimer’s disease, cardiovascular and respiratory diseases, diabetes mellitus and even the development of cancer. Traditional tobacco smokers and e-cigarette users are particularly exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 180 publications
2
20
0
Order By: Relevance
“…In conclusion, we report for the first time that acrolein induces an increase in [Zn 2 ⁺]ᵢ levels by stimulating the mitochondrial oxidative stress production pathway. For some respiratory diseases, such as COPD or cancer, the latest study has shown that ROS production induced by acrolein is closely related to the occurrence and development of diseases (Hikisz and Jacenik, 2023). Another study showed that intracellular Zn 2 ⁺ can be increased in a short period of time by ROS, which may be an antioxidant feedback mechanism (Truong-Tran et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we report for the first time that acrolein induces an increase in [Zn 2 ⁺]ᵢ levels by stimulating the mitochondrial oxidative stress production pathway. For some respiratory diseases, such as COPD or cancer, the latest study has shown that ROS production induced by acrolein is closely related to the occurrence and development of diseases (Hikisz and Jacenik, 2023). Another study showed that intracellular Zn 2 ⁺ can be increased in a short period of time by ROS, which may be an antioxidant feedback mechanism (Truong-Tran et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…From the volatile organic compounds (VOCs) listed among the chemical components of the emissions of 3D printers, acrolein is a potential concern from the perspective of lung carcinogenicity (Hikisz & Jacenik, 2023). However, IARC found the evidence regarding cancer in humans caused by acrolein exposure inadequate (IARC, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the IARC's (2017) compilation of carcinogens, ACR was classified as “not classifiable as to its carcinogenicity to humans” (Group 3). However, extensive research has established a significant association between ACR and prevalent chronic illnesses, such as Alzheimer's disease (AD) (Lovell et al., 2001), Parkinson's disease (Jomova et al., 2010), and respiratory cancers (Hikisz & Jacenik, 2023).…”
Section: Influence Of Anthocyanins On Contaminants From Food Processingmentioning
confidence: 99%